Markers of extracellular matrix remodeling and systemic inflammation in patients with heritable thoracic aortic diseases - Seim, Bjørn Edvard; Holt, Margrethe Flesvig; Ratajska, Aleksandra; Michelsen, Annika; Ringseth, Monica Myklebust; Halvorsen, Bente Evy; Skjelland, Mona; Kvitting, John-Peder Escobar; Lundblad, Runar; Krohg-Sørensen, Kirsten; Osnes, Liv T. N.; Aukrust, Pål; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: In approximately 20% of patients with thoracic aortic aneurysms or dissections a heritable thoracic aortic disease (HTAD) is suspected. Several monogenic connective tissue diseases imply high risk of aortic disease, including both non-syndromic and syndromic forms. There are some studies assessing inflammation and extracellular matrix remodeling (ECM) in patients with non-hereditary aortic disease, but such studies in patients with hereditary diseases are scarce. Aims: To quantify markers of ECM and inflammation in patients with vascular connective tissue diseases versus healthy controls. Methods: Patients with Loeys-Dietz syndrome (LDS, n=12), Marfan syndrome (MFS, n=11), and familial thoracic aortic aneurysm 6 (FTAA6, n=9), i.e. actin alpha 2 (ACTA2) pathogenic variants, were recruited. Exome or genome sequencing was performed for genetic diagnosis. Several markers of inflammation and ECM remodeling were measured in plasma by enzyme immunoassays. Flow cytometry of T cell subpopulations was performed on a subgroup of patients. For comparison, blood samples were drawn from 14 healthy controls. Results: (i) All groups of HTAD patients had increased levels matrix metalloproteinase-9 (MMP-9) as compared with healthy controls, also in adjusted analyses, reflecting altered ECM remodeling. (ii) LDS patients had increased levels of pentraxin-3 (PTX3), reflecting systemic inflammation. (iii) LDS patients had increased levels of soluble CD25, a marker of T cell activation. Conclusion: Our data suggest that that upregulated MMP-9, a matrix degrading enzyme, is a common feature of several subgroups of HTAD. In addition, LDS patients as increased levels of PTX3 reflecting systemic and in particular vascular inflammation.